2023
DOI: 10.1159/000530056
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clinical Parameters and Induction Regimens on Peripheral Blood Stem-Cell Mobilization and Collection in Multiple Myeloma Patients

Sandra Sauer,
Lennart Hieke,
Julia Brandt
et al.

Abstract: Introduction: High-dose chemotherapy (HDCT) followed by autologous blood stem-cell transplantation (ABSCT) remains the standard consolidation therapy for newly diagnosed eligible multiple myeloma (MM) patients. As a prerequisite, peripheral blood stem cells (PBSCs) must be mobilized and collected by leukapheresis (LP). Many factors can hamper PBSC mobilization/collection. Here, we provide a comprehensive multiparametric assessment of PBSC mobilization/collection outcome parameters in a large cohort. Methods: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Despite the lower yields and increased plerixafor use in the daratumumab-containing regimens in the NDMM setting across the MASTER, GRIFFIN, and CASSIOPEIA trials, the integration of daratumumab into the PI-IMIds triplet therapy did not negatively affect the feasibility and safety of conducting ASCT or hinder successful engraftment. Several retrospective clinical trials have described HSC mobilization and collection in patients receiving daratumumab-based induction regimens [44][45][46].…”
Section: Stem Cell Mobilization and Harvestingmentioning
confidence: 99%
“…Despite the lower yields and increased plerixafor use in the daratumumab-containing regimens in the NDMM setting across the MASTER, GRIFFIN, and CASSIOPEIA trials, the integration of daratumumab into the PI-IMIds triplet therapy did not negatively affect the feasibility and safety of conducting ASCT or hinder successful engraftment. Several retrospective clinical trials have described HSC mobilization and collection in patients receiving daratumumab-based induction regimens [44][45][46].…”
Section: Stem Cell Mobilization and Harvestingmentioning
confidence: 99%
“…This method required invasive bone marrow aspirations and was associated with limited yields. Consequently, it was gradually supplanted by the use of peripheral blood stem cells (PBSCs), which could be collected via leukapheresis, offering higher stem cell yields and a less invasive procedure [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the availability of stored PBSC grafts, salvage ASCT is not always performed due to various factors such as deterioration in performance [ 12 ], status, or therapy-related comorbidities. Furthermore, a cost utilization analysis conducted in 2013 revealed that a substantial proportion of patients had PBSC products remaining unused in prolonged cryopreservation after the initial ASCT [ 3 , 13 ]. This surplus stemmed from the estimated cost of collecting and storing PBSCs beyond that required for a single ASCT, accounting for approximately one-third of total costs.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding patients with multiple myeloma, Jantunen et al comprehensively analyzed current mobilization strategies [1]. The impact of clinical parameters and induction regimens on peripheral blood stem cell (PBSC) mobilization in a large cohort of multiple myeloma patients has been evaluated by Sauer and colleagues [2]. In a more specific approach, Sauer et al [3] assessed in a second study the effectiveness of autologous stem cell collection after daratumumab-VTD versus VCD.…”
mentioning
confidence: 99%